2021
DOI: 10.2478/bhk-2022-0005
|View full text |Cite
|
Sign up to set email alerts
|

Balance, physical conditioning, and health perception in elderly women submitted to a 32-week physical exercise program

Abstract: Study aim: To assess the effects of a long-term physical exercise program on balance, physical conditioning, and health perception in elderly women. Material and methods: The sample, 143 elderly women, were randomly assigned to an experimental group (EG; n = 71; age: 71.62 ± 4.96 years) and control group (CG; n = 72; age: 72.89 ± 5.40 years). The EG was submitted to a 32-week physical exercise program (3×/week, 60 min/session). Balance and physical conditioning were assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…This test requires controlling whole body acceleration in the vertical and fore–aft directions. The older adults in our study performed the test within the ranges reported in the literature (5.1 to 9.0 s) [ 46 , 47 , 48 , 49 , 50 ]. There was no statistically significant improvement in performance, since the results at entry into the study were typical for this age group.…”
Section: Discussionmentioning
confidence: 99%
“…This test requires controlling whole body acceleration in the vertical and fore–aft directions. The older adults in our study performed the test within the ranges reported in the literature (5.1 to 9.0 s) [ 46 , 47 , 48 , 49 , 50 ]. There was no statistically significant improvement in performance, since the results at entry into the study were typical for this age group.…”
Section: Discussionmentioning
confidence: 99%
“…However, this assessment is subjective and does not necessarily correspond to the actual level of stress exposure [56]. In addition to physical activity, studies have also analyzed physical fitness, which in itself, as physical resistance to a stressor, or indirectly through psychological benefits (e.g., higher self-esteem, endurance) [57], may facilitate coping with stress. It is difficult to separate the effects of these two variables (physical activity and physical fitness) as they are correlated to some extent.…”
Section: Stress and Physical Activitymentioning
confidence: 99%